1, 2, 4‐Triazole Links and N‐Azo Bridges Yield Energetic Compounds. Issue 32 (30th June 2015) - Tang, Yongxing; Gao, Haixiang; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract Triazole links and polynitropyrazole rings give rise to compounds with energetic properties. These materials were fully characterized by NMR and infrared spectroscopy, elemental analysis, and differential scanning calorimetry (DSC). In addition, the structures of compounds 5 and 8 were confirmed by single‐crystal X‐ray diffraction analysis. Detonation properties, calculated from heats of formation and experimental densities, thermal stabilities, and impact and friction sensitivities support the potential use of these materials for explosive applications.